Hospitalized Patients' Perceived Knowledge and Risk of Monoamine Oxidase Inhibitor Medications Before and After a Pharmacist's Classroom-Based Education - Richard G. Wenzel, Pharm.D; Jon C. Schommer, Ph.D (University of Minnesota Libraries Publishing, 2010)
Objective: Assess if a classroom-based pharmacy education service for hospitalized headache patients newly prescribed a monoamine oxidase inhibitor (MAOI) results in, 1) higher self-perceived medication knowledge, or 2) lower perceived risk of using MAOIs.Subjects: Individuals admitted to an inpatient headache unit over a five month periodMethods: Patient survey administered before and after the education service to any patient newly prescribed an MAOI. Results: Seventy-eight individuals completed the study. Paired-samples t-tests showed that for each of the four items related to selfperceived medication knowledge, the scores reflected higher knowledge after the MAOI class compared to before the class (p < 0.05). For three out of the four items related to perceived risk of using MAOIs, the scores reflected a lower level of perceived risk after the MAOI class compared to before the class (p < 0.05). One item did not significantly change: "The MAOI prescribed for me is just as good as other products available for treating headache."Conclusion: Our results demonstrate a pharmacist-conducted, classroom-based teaching method for newly prescribed MAOI patients can result in higher self-perceived medication knowledge and lower perceived risks.